Analysis of Service Quality, Price and Customer Experience on Customer Satisfaction at PT Maritim Era Sukses - Callista Fausta; Purnama Yanti Purba; Deniss Phelandy; Willyanto Wijaya; Alwin (Institute of Computer Science (IOCS), 2021)
This research intends to test and analyze the effect of service quality, price, customer experience on customer satisfaction at PT Maritim Era Sukses Medan. The phenomenon of a decrease in purchasing decisions from those experiencing a decline from declining sales data, offering expedition prices that are more expensive than other companies with comparable services and services, customer experience regarding complaints from customers when getting service from employees in the form of a process that is considered slow in processing dealing with lost products, often not answering calls from customers are the background of this research. Simple random sampling was used as a method for taking samples. The sample used is 100 people. Data analysis method using multiple linear regression. In partial data testing, the variables of service quality show a positive and significant influence on customer satisfaction at PT Maritim Era Sukses, price show a positive and significant influence on customer satisfaction at PT Maritim Era Sukses, customer experience show a positive and significant influence on customer satisfaction at PT Maritim Era Sukses . In testing the data analysis simultaneously, the variables of service quality, price, customer experience show a positive and significant influence on customer satisfaction at PT Maritim Era Sukses.